Manajemen Pendidikan Karakter Religious dalam Pembelajaran (Studi Multikasus di MAN 1 Lombok Tengah dan SMAN 1 Praya) - L. Gde M. Rahiqil Maktum; Lukman Hakim; Fathurrahman Muhtar (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Globalization has a significant impact on various aspects of life, including character education in Indonesia. Character education is a fundamental foundation in forming a generation with integrity, morals, and strong national values. This study aims to analyze strategic management in fostering religious character education in MAN 1 Central Lombok and SMAN 1 Praya. This study uses a qualitative approach with data collection methods through interviews, observations, and documentation. The research was carried out for six months involving the principal, deputy principal for curriculum, student affairs, and public relations, as well as teachers, students, and parents. Data analysis uses the Miles and Huberman interactive model which consists of data reduction, data presentation, and conclusion retrieval and submission. The results of the study show that the planning of religious character education is carried out at the beginning of the new school year through coordination between the principal, curriculum, student affairs, and teachers in formulating policies outlined in school rules, rules, as well as syllabus and lesson plans. The implementation of religious character education is carried out through various activities, such as flag ceremonies, discipline, cleanliness of the school environment, the implementation of congregational prayers, the integration of character values in subjects, and the example of teachers. The main supporting factors in fostering religious character education include the active role of teachers in providing examples, guidance, and advice, as well as support from parents and the community. With the implementation of the right strategies, religious character education can be effectively integrated into the formal education system.